2013
DOI: 10.1016/j.jpha.2013.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of five diterpenoid alkaloids in Herba Delphinii by HPLC/ELSD

Abstract: A HPLC–ELSD method was developed and validated for simultaneous determination of five Hetisane-type diterpenoid alkaloids in a Tibetan traditional herbal medicine, “Gebu Dilu” (Herba Delphinii), using a Kromasil C18 column (250 mm×4.6 mm, 5 μm) with the mobile phase consisting of acetonitrile and 0.1% triethylamine in gradient (detected by evaporative light scattering detector). The linear ranges of five compounds were determined and method validation was evaluated completely. The established method is rapid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Therefore, this study focuses on overcoming these problems by using a combination of HPLC and ELSD. ELSD is a general-purpose detector that can detect organic substances without ultraviolet absorption, and has a very important application in chromatographic analysis [13][14][15][16]. To our knowledge, this study was the first time that HPLC method had been applied for the determination of TEA, TIPA and DEIPA in liquid cement grinding aids.…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, this study focuses on overcoming these problems by using a combination of HPLC and ELSD. ELSD is a general-purpose detector that can detect organic substances without ultraviolet absorption, and has a very important application in chromatographic analysis [13][14][15][16]. To our knowledge, this study was the first time that HPLC method had been applied for the determination of TEA, TIPA and DEIPA in liquid cement grinding aids.…”
Section: Introductionmentioning
confidence: 96%
“…For the analysis of total alkaloids, in addition to qualitative identification, it is also necessary to determine the appropriate analytical method for quantitative determination of compound content in Annona muricata L. [18]. Analytical methods include using chemometrics, HPLC, UV Spectrophotometer -Vis for determination of total alkaloid content was carried out on various plant extracts [19]- [25]. Therefore, an analysis of total alkaloids was developed using reverse phase HPLC on soursop leaf ethanol extract samples using caffeine standard as a comparison.…”
Section: Introductionmentioning
confidence: 99%
“…The soxhletation technique has also been developed to separate alkaloids from other metabolites. [19] reported that optimization under HPLC conditions in the analysis of alkaloids in herbal plants using acetonitrile (A) and 0.1% triethylamine as the mobile phase in gradient as 30% A (0 -21 min), 30% A-45% A (21-30 min), 45% A-55% A (30-55 min) at a flow rate of 1.0 mL/min. In Guo's research, 2016 reported an analysis of the isoquinoline alkaloid group using GCMS under conditions of the organic phase was kerosene with rubber emulsifier (1:15.25, v:v), acetic acid (36%) as carrier.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, ve diterpenoid alkaloids in Herba delphinii were determined by HPLC with a mobile phase consisting of acetonitrile and 0.1% triethylamine in gradient, here, triethylamine is a silanol masking agent. 25 Nowadays, with the unique advantage of ionic liquids on the contribution to the retention of alkaloids, ionic liquids have become common mobile phase additives in HPLC. In 2003, ephedrine was separated by HPLC with 1-alkyl-3-methylimidazolium-based ionic liquid as the eluent.…”
Section: Introductionmentioning
confidence: 99%